Pelvic Floor Ultrasound for the Evaluation of Urethral Mobility in Women with Stress Urinary Incontinence: A Literature Review - Sania Utari; Edy Fakhrizal (Indonesian Journal of Obstetrics & Gynecology Science, 2026)
Introduction: Stress urinary incontinence (SUI) is the most common urinary incontinence in women, mainly associated with urethral hypermobility and reduced intrinsic sphincter function. Transperineal pelvic floor ultrasound (PFU) is a minimally invasive, low-cost imaging method that quantifies urethral mobility through bladder neck descent (BND), urethral rotation angle (URA), and retrovesical angle (RVA).Objectives: To summarize available evidence on PFU diagnostic performance and its potential clinical role in identifying urethral hypermobility in women with SUI.Methods: This literature review focuses on transperineal PFU as a noninvasive approach to assess urethral hypermobility, primarily using BND, URA, and RVA measurements.Results: Multiple studies report PFU provides reproducible measurements with acceptable sensitivity and specificity for diagnosing SUI. Although cutoff values for URA and RVA vary depending on study quality and methodology, these parameters consistently serve as key indicators of urethral hypermobility. Compared with standard invasive techniques, PFU improves patient comfort, offers real-time dynamic visualization, and allows greater clinical flexibility.Conclusion: PFU is a promising adjunct for diagnosing passive urethral hypermobility and may reduce reliance on invasive tests while maintaining accuracy. Larger studies are needed to standardize protocols and validate cutoff values across diverse populations. AbstrakPendahuluan: Stress urinary incontinence (SUI) merupakan jenis inkontinensia urin yang paling sering pada perempuan, terutama berkaitan dengan hipermobilitas uretra dan penurunan fungsi sfingter intrinsik. Ultrasonografi dasar panggul (PFU) transperineal adalah metode pencitraan yang minim invasif dan berbiaya rendah untuk menilai mobilitas uretra secara kuantitatif melalui penurunan leher kandung kemih (BND), sudut rotasi uretra (URA), dan sudut retrovesikal (RVA).Tujuan: Merangkum bukti yang tersedia mengenai kinerja diagnostik PFU serta potensi perannya dalam praktik klinis untuk mengidentifikasi hipermobilitas uretra pada perempuan dengan SUI.Metode: Tinjauan pustaka ini berfokus pada PFU transperineal sebagai metode noninvasif untuk menilai hipermobilitas uretra, dengan parameter utama berupa BND, URA, dan RVA.Hasil: Berbagai studi melaporkan bahwa PFU menghasilkan pengukuran yang reprodusibel dengan sensitivitas dan spesifisitas yang dapat diterima untuk diagnosis SUI. Meskipun nilai ambang URA dan RVA bervariasi bergantung pada kualitas dan metodologi studi, kedua parameter tersebut secara konsisten menjadi indikator penting hipermobilitas uretra. Dibandingkan teknik invasif standar, PFU meningkatkan kenyamanan pasien, menyediakan visualisasi dinamis secara real-time, dan menawarkan fleksibilitas klinis yang lebih tinggi.Kesimpulan: PFU merupakan pemeriksaan tambahan yang menjanjikan untuk mendiagnosis hipermobilitas uretra pasif dan berpotensi mengurangi ketergantungan pada tes invasif tanpa menurunkan akurasi. Namun, diperlukan studi berskala lebih besar untuk menstandardisasi protokol dan memvalidasi nilai ambang pada berbagai populasi.